2018
DOI: 10.1038/s41598-018-19622-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucansucrase (mutant) enzymes from Lactobacillus reuteri 180 efficiently transglucosylate Stevia component rebaudioside A, resulting in a superior taste

Abstract: Steviol glycosides from the leaves of the plant Stevia rebaudiana are high-potency natural sweeteners but suffer from a lingering bitterness. The Lactobacillus reuteri 180 wild-type glucansucrase Gtf180-ΔN, and in particular its Q1140E-mutant, efficiently α-glucosylated rebaudioside A (RebA), using sucrose as donor substrate. Structural analysis of the products by MALDI-TOF mass spectrometry, methylation analysis and NMR spectroscopy showed that both enzymes exclusively glucosylate the Glc(β1→C-19 residue of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 41 publications
1
25
1
1
Order By: Relevance
“…18,21,31 Finally, the importance of residue Q1140 was shown in a study where Gtf180-ΔN was used to transglycosylate steviol glycosides. 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,21,31 Finally, the importance of residue Q1140 was shown in a study where Gtf180-ΔN was used to transglycosylate steviol glycosides. 15…”
Section: Discussionmentioning
confidence: 99%
“…1,3,10,11 These products are attracting strong interest for industrial applications as food or feed ingredients and in pharmacy and medicine. 1215…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has shown that plant‐derived glucosyltransferases such as UGT76G1 (Wang et al., ) can insert and produce rebaudioside A from stevioside in Saccharomyces cerevisiae (Olsson et al., ; Li et al., ) and Escherichia coli system (Wang et al., ). Production of rebaudioside I, rebaudioside D, and glucosyl rebaudioside A from rebaudioside A by enzymatic biotransformation has also been reported (Gerwig, Te Poele, Dijkhuizen & Kamerling, ; Te Poele et al., ; Chen et al., ). Lactobacillus reuteri 180 glucansucrase can transferred several glucosyl residues from one moiety to nine moieties into rebaudioside A from sucrose (Gerwig et al., ).…”
Section: Introductionmentioning
confidence: 89%
“…Although there have been many biotransformation trials for stevioside or rebaudioside A, cyclomaltodextrin glucanotransferase is the most well‐known enzyme for stevioside derivatives and the sole one used in industrial production of enzymatically modified stevioside. To elucidate the structure‐sweetness relationship, the stevioside or rebaudioside A derivatives produced by cyclomaltodextrin glucanotransferase, glucansucrase from L. citreum (Ko et al., ), β‐fructofuranosidase, or glucansucrase from Lactobacillus returi by transglucosylation (Te Poele et al., ). However, the structure‐sweetness relationship of various steviol derivatives remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This α-1→6 glycosylated reb A compound was reported to have a superior taste profile, with significantly less bitterness than the parent reb A. In fact, the author claimed that it displayed almost no bitterness at all [15]. Reb A was also modified by using the method previously described for reb C, and the product is highly likely to contain the same α-1→6 glycosylated reb A, although it has not been fully characterized (Figure 3).…”
Section: Introductionmentioning
confidence: 99%